Reflection Plus 4: Classifying Alternate Perspectives in Experiential Learning - Tara Fenwick (Adult Education Research Conference, 1999)
This paper presents five theoretical perspectives that can inform experiential learning. A rationale for this typology is outlined briefly, then each perspective is described according to learning dimensions such as view of knowledge, learner, power, and role of educator. A chart summary comparing these perspectives will be distributed at the session.